SPELLING BEE GAME IN TEACHING NARRATIVE TEXT - RAHAYU, Jeani Shinta (2009)
Currently, the students, especially students in senior high school level must deal with many kinds of text. One kind of text that must be learned by the students is narrative text. Meanwhile, the text should be learned through a meaningful activity. One kind of the effective activity is by having a game. This study was aimed to observe the use of Spelling Bee game in teaching narrative text, and to find out the obstacles, advantages and disadvantages of using Spelling Bee game in learning about narrative text. This study was conducted by using a quasi-experimental design with pretest and posttest nonequivalent groups design. Two classes of the first grader in SMAN 5 Cimahi were chosen as the sample in this study. There were 40 students in each class. The findings of this study suggested that Spelling Bee was effective in improving students' understanding on narrative text as indicated by a statistically higher reading score of experimental group students (M = 76.0, SE = 1.11) than control group students (M = 60.5, SE = 1.31) in the posttest. This difference was highly significant t (78) = 8.982, p < 0.05 with the effect size value r = 0.74. In addition, the students' answer on the questionnaire showed that the students' inability in recognizing an English alphabet became the obstacle during the process. Besides, students' improvement on spelling skill was the advantage and limitation of time was the disadvantages of using Spelling Bee game in teaching narrative text. There were two main conclusions that can be drawn from the present study. First, Spelling Bee could improve student' reading comprehension on narrative text. Second, Spelling Bee game was appropriate for the students in senior high school level. Since Spelling Bee was very appropriate to apply for students who had a good spelling skill. For teachers who are interested in using Spelling Bee game, it is suggested to ensure that the students' do not have problems with spelling. In addition for further study, it would be very excellent if the Spelling Bee game can be used in other genres.